2010
DOI: 10.12693/aphyspola.118.1059
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ex Situ MgB2Barrier and HIP on the IcAnisotropy in Double Core MgB2/Cu Wires

Abstract: The effect of large I c anisotropy reductions in MgB 2 /Cu sheathed wire is presented. The measurements of the critical current in rising magnetic field up to 14 T at 4.2 K were performed. Due to the application of the high isostatic pressure process to the copper sheathed MgB 2 wires with the ex situ MgB 2 homo barrier around the in situ core the anisotropy for such wires was very small and approached to less than 2% at magnetic field over 4 T. The presented geometry and technology show several advantages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The studies presented by Hossain et al, Li et al, and Gajda et al showed that the value of critical current has the same value for the short and long samples [12][13][14]. Critical current measurements were made in the International Laboratory of High Magnetic Fields and Low Temperatures in Wroclaw [12,15]. Our studies were performed on MgB 2 wires obtained from Institute of High Pressure PAS and Hyper Tech Research, Inc. [16,17]).…”
Section: Methodsmentioning
confidence: 92%
“…The studies presented by Hossain et al, Li et al, and Gajda et al showed that the value of critical current has the same value for the short and long samples [12][13][14]. Critical current measurements were made in the International Laboratory of High Magnetic Fields and Low Temperatures in Wroclaw [12,15]. Our studies were performed on MgB 2 wires obtained from Institute of High Pressure PAS and Hyper Tech Research, Inc. [16,17]).…”
Section: Methodsmentioning
confidence: 92%